"Being downcast by society… adds to the stress levels and would explain why [we] smoke more.": Smoking among HIV-positive Black men who have sex with men. Issue 1 (2nd January 2021) - del Pino, Homero E.; Dacus, Jagadisa-devasri; Harawa, Nina T.; McWells, Charles
Abstract: Smoking causes more deaths among people living with HIV than HIV infection itself. Few smoking cessation interventions and studies of sexual minority communities have considered the lived experiences of Black men who have sex with men (BMSM) living with HIV. Before developing interventions for these men, we need to answer: How do experiences of discrimination and stigma influence their perceptions of smoking? This phenomenological study was led by a community-based organization. We conducted six focus groups with 53 BMSM living with HIV in Los Angeles. We used minority stress theory in the analysis and interpretation of the data. We identified two themes: (1) co-occurrence of race and sexual orientation stressors and smoking (e.g., "I feel like I'd be discriminated against sometimes because I'm gay and because I'm Black.") and (2) smoking as a reaction to HIV-positive status (e.g., "I know more people that started smoking after they found out they [had] HIV."). Participants smoked to cope with stressors around race, sexual orientation, and living with HIV. These findings challenge us to ensure that smoking cessation interventions address the personal and social concerns of BMSM living with HIV and help them identify healthier ways to cope with stressors.